PENGARUH LATIHAN HIGH KNEE BOX JUMP TERHADAP DAYA LEDAK OTOT TUNGKAI PEMAIN PUTRA CLUB BOLA VOLI KILAT KOTA PADANG - Febby Mardesryadi; Gusril Gusril (JURNAL STAMINA, 2019)
The problem in this research is the low explosive yield ability of limb muscles of athlete Club Lightning Padang city, so that at the time of exercise or match the athletes are not effective in performing the block and smash. This research aims to know the influence of exercise high knee box jump against explosive limb muscles Lightning volleyball Club athletes of Padang city. This type of research is quasi experiment, this research was carried out in June-July 2018 in volleyball Club Lightning Padang city. The population in this study amounted to 18 people. Sampling using a purposive sampling technique with a total of 12 people, instruments used in this research is a test of explosive limb muscles using the Vertical Jump. Technique of data analysis used in this study using a t-Test test. The results of this research show there is a high knee exercises influence box jump toward an explosive athlete's limb muscles Lightning volleyball Club's Padang city, proved to be due to thitung larger than the 6.36 ttabel 1.812.